Effect of Joule Heating and Thermal Radiation of MHD Boundary Layer Oldroyd-B Nanofluid Flow with Heat Transfer over a Porous Stretching Sheet by Finite Element Method. (3rd October 2022) - Ullah, Hakeem; Fiza, Mehreen; Khan, Kamal; Batool, Shamaila; Ghufran, S. M.; Al-Mekhlafi, Seham M.
Abstract : In this study, an incompressible two-dimensional Oldroyd-B nanofluid steady flow past a stretching sheet considering the outcomes of magneto-hydrodynamics (MHD) and porous medium with magnetic, electrical, and thermal radiation effects is investigated. Using a similarity transformation, the governing equations in the form of partial differential equations (PDEs) are converted into a nonlinear ordinary differential equations (ODEs) system. The acquired system is numerically solved by the finite element method (FEM). The effects of physical parameters like Deborah numbers "β 1 " and "β 2 ", Brownian motion "N b ", thermophoresis parameter "N t ", Prandtl parameter "Pr ", Lewis number "L e ", thermal conductivity "k ", dynamic viscosity " μ ", magnetic and electric effects as "M " and "E 1 ", and thermal radiation effect "Rd " on the flow are studied in detail. For higher N b values, regional Nusselt numbers are increasing in magnitude. The local Sherwood number's size rises for high N b numbers.